Pantanal’s fish native meatballs has the nutritional values increased with the use of pequi in its recipe - Pereira, Queila Dias; Kwiatkowski, Angela; Munhoz, Cláudia Leite; Porto, Ricardo Santos; Costa, Celso Soares; Curvo, Lucimar Rodrigues Vieira; Diemer, Odair (Acta Scientiarum. Animal Sciences, 2021)
The study aimed to evaluate whether the addition of pequi increases the nutritional value of meatballs made with piranha and pacu fillets. Piranhas were obtained from the colony of fishermen; pacu with the fish farmer and the pequis were collected in nature. Fish were filleted and triturated, and the resulting masses were used to prepare 4 types of meatballs: piranha fillet with 2.0% pequi pulp, piranha fillet without pequi pulp, pacu fillet with with 2.0% pequi pulp, and pacu fillet without pequi pulp. After preparation, acceptance, purchase intention and frequency of consumption were evaluated with untrained tasters. Chemical composition parameters evaluated were crude protein, lipids, ash, moisture, carotenoids and antioxidant activity. Results of acceptability for all formulations were similar. The chemical composition of piranha meatballs presented differences (p < 0.05) for lipids and carotenoids. Pacu meatballs showed no difference (p > 0.05) for moisture, carotenoids, and antioxidant activity. The addition of pequi did not alter the organoleptic characteristics, however increased the nutritional values, therefore, it can add value to the product to be marketed and be more nutritionally attractive to the consumer.